2021
DOI: 10.3390/fluids6100363
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Dynamic Maps of Disc Brakes under Different Operating Conditions

Abstract: The operating conditions during the braking process in an automobile affect the tribological contact between the pad and disc brake, thus, influencing the times and distances of braking and, in a more significant way, the safety of the braking process. This mathematical work aimed to provide a general visualization of the disc brake’s mechanical, dynamic, and thermal behavior under different operating conditions through 2D maps of the power dissipated, braking time, and braking distance of a disc brake with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…From the results achieved, it can be concluded that vehicles 1 and 4 had insufficient braking values during the stationary test due to lower braking forces measured on the cylinder brake test bench. According to García-León et al (2021) and Gurumoorthy et al (2021), insufficient values of braking forces can be caused by malfunctions of the vehicle´s brake system, such as excessive wear of brake discs and brake linings, insufficient pressure in the brake system, which is caused by air leak on the master brake cylinder. In another case, the insufficient values of braking forces can also be caused by the pollution of vehicle´s tires or the cylinders of the brake seat and, last but not least, by insufficient pressure in the tires, as stated by Senabre et al (2012b) They indicate that by changing the tire pressure, it is possible to obtain incorrect braking force results on the brake cylinder test bench, which implies that tire pressure is a determining factor in assessing the condition of the vehicle´s braking system.…”
Section: Decelerometer Vmz 300mentioning
confidence: 99%
“…From the results achieved, it can be concluded that vehicles 1 and 4 had insufficient braking values during the stationary test due to lower braking forces measured on the cylinder brake test bench. According to García-León et al (2021) and Gurumoorthy et al (2021), insufficient values of braking forces can be caused by malfunctions of the vehicle´s brake system, such as excessive wear of brake discs and brake linings, insufficient pressure in the brake system, which is caused by air leak on the master brake cylinder. In another case, the insufficient values of braking forces can also be caused by the pollution of vehicle´s tires or the cylinders of the brake seat and, last but not least, by insufficient pressure in the tires, as stated by Senabre et al (2012b) They indicate that by changing the tire pressure, it is possible to obtain incorrect braking force results on the brake cylinder test bench, which implies that tire pressure is a determining factor in assessing the condition of the vehicle´s braking system.…”
Section: Decelerometer Vmz 300mentioning
confidence: 99%